Ways to Achieve the Dimensions of Sustainable Development at The Yemeni University of Saada and its Importance; From the Point of View of Academic Leaders and Faculty Working in it - Dahesh, AbdulRahman Muhammad; Amin, AbdulJabbar AlTayyib (Journal of Educational and Psychological Sciences, 2023)
The aim of the research is to find out ways to achieve the dimensions of sustainable development in the Yemeni University of Saada and their importance from the point of view of the academic and administrative leaders and the teaching staff working in the university. Divided into five dimensions: (environmental, social, educational, economic, and technical), which were applied to a purposive sample of academic leaders and faculty members, which were selected using a comprehensive enumeration method. The results of the study showed that the overall tool obtained an average of (4.15 out of 5), with a general verbal grade (high), and at the level of the main dimensions, the technical dimension ranked first with an average of (4.31), and secondly; The economic dimension, with an average of (4.24), and thirdly; The environmental and social dimension, with an average of (4.09), and finally; The educational dimension averaged (4.04).In light of the research results, the researcher recommended the necessity of activating the university's role in achieving all ways of sustainable development dimensions, developing the university's sustainable technical infrastructure, introducing sustainability concepts and environmental education courses in the university's curricula and majors, in addition to proposals aimed at improving and developing the university's role in achieving sustainable development through studies. complementary to the topic.
Keywords: dimensions of sustainable development; Saada University; Yemen; academic leaders and faculty